Concise enantioselective synthesis of (+)-decarestrictine L via proline-catalyzed sequential alpha-aminooxylation and Horner-Wadsworth-Emmons olefination - Rawat, Varun; Chouthaiwale, Pandurang V.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2009)
A short enantioselective synthesis of (+)-decarestrictine L, a cholesterol biosynthesis inhibitor metabolite, is described using a D-proline catalyzed sequential alpha-aminooxylation and a Horner-Wadsworth-Emmons olefination. (C) 2009 Elsevier Lid All rights reserved

Facile enantioselective synthesis of (S)-N-(5-chlorothiophene-2-sulfonyl)-beta,beta-diethylalaninol via proline-catalyzed asymmetric alpha-aminooxylation and alpha-amination of aldehyde - Rawat, Varun; Chouthaiwale, Pandurang V.; Chavan, Vilas B.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2010)
A high-yielding enantioselective synthesis of the bioactive (S)-N-(5-chlorothiophene-2-sulfonyl)beta,beta-diethylalaninol (1), a Notch-1-sparing gamma-secretase inhibitor metabolite (with EC50 = 28 nM) effective in reduction of All production in vivo, has been realized starting from readily available 3-pentanone. The key steps of the synthesis are proline-catalyzed alpha-aminooxylation and alpha-amination of aldehyde: the latter contributing an overall yield of 45.2% and 98% ee. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: alpha-Amination; alpha-Aminooxylation; Alzheimer's disease; Amino alcohol; Proline

Novel synthesis and characterization of titanium superoxide and its application in organic oxidative processes - Reddy, R. Santhosh; Shaikh, Tanveer Mahamadali; Rawat, Varun; Karabal, Pratibha U.; Dewkar, Gajanan; Suryavanshi, Gurunath; Sudalai, Arumugam (Catalysis Surveys from Asia, 2010)
A novel, exceptionally stable titanium superoxide radical ion was prepared and its structure determined by FTIR, ESR, Raman spectroscopy, X-ray diffraction, thermogravimetric/differential thermal analysis and elemental analysis. This heterogeneous catalyst has been found to be effective for the selective oxidation of aromatic amines and phenols to the corresponding nitro aromatics and p-quinones, respectively. In addition, this non-toxic, inexpensive and reusable catalyst has also been used in aminobromination of olefins, which proceed to give the 1, 2-bromoaminated anti-Markovnikov product. A brief account of these results is summarized in this review.
Keywords: Amino Bromination; Anti-Markovnikov; heterogeneous catalyst; Oxidation; Titanium superoxide

Asymmetric synthesis of (+)-stagonolide C and (-)-aspinolide A via organocatalysis - Shelke, Anil M.; Rawat, Varun; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2012)
A new enantioselective synthesis of two important fungal metabolites, (+)-stagonolide C and (-)-aspinolide A, has been described from readily available raw materials. Praline catalyzed asymmetric alpha-aminooxylation and Jorgensen's epoxidation of aldehydes are the key reactions employed in the introduction of chirality. The formation of the 10-membered lactone core structure was finally accomplished via Steglich esterification and ring closing metathesis reactions. (C) 2012 Elsevier Ltd. All rights reserved.

Pd-catalyzed selective hydrosilylation of aryl ketones and aldehydes - Chouthaiwale, Pandurang V.; Rawat, Varun; Sudalai, Arumugam (Tetrahedron Letters, 2012)
Pd salts in combination with triethylsilane as hydride source and DMF as solvent has been found to be excellent catalytic combination that selectively reduces aryl ketones and aldehydes under mild conditions to afford triethylsilyloxy compounds in excellent yields. Product selectivity to the respective benzyl alcohols can however be achieved when the reaction was performed in DMF/H2O (4:1) as solvent system. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; Hydrosilylation; Ketones; Palladium; Triethylsilane

Proline catalyzed sequential alpha-aminooxylation or -amination/reductive cyclization of o-nitrohydrocinnamaldehydes: a high yield synthesis of chiral 3-substituted tetrahydroquinolines - Rawat, Varun; Kumar, B. Senthil; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2013)
A new sequential organocatalytic method for the synthesis of chiral 3-substituted (X = OH, NH2) tetrahydroquinoline derivatives (THQs) [ee up to 99%, yield up to 87%] based on alpha-aminooxylation or -amination followed by reductive cyclization of o-nitrohydrocinnamaldehydes has been described. This methodology has been efficiently demonstrated in the synthesis of two important bioactive molecules namely (-)-sumanirole (96% ee) and 1-[(S)-3-(dimethylamino)-3,4-dihydro-6,7-dimethoxy-quinolin-1(2H)-yl]- propanone (92% ee).